Integrated Protocols to Ensure Security Services in Wireless Sensor Networks. (28th July 2013) - Faisal, Mohammed; Al-Muhtadi, Jalal; Al-Dhelaan, Abdullah
Abstract : Security in current/next generation wireless sensor network (WSN) is challenging, due to its special characteristics and the scarcity of energy, and processing power. Thus, many security methods are trying to solve the problem of security in wireless sensor networks. Many of these methods use symmetric cryptography, and others use asymmetric cryptography. Security in WSN demands authentication, confidentiality, integrity, balancing the energy cost, nonreputation, and scalability services. In this paper, we introduce two protocols to address these main security services. The proposed protocols integrate public key and symmetric key algorithms to ensure optimal usage of sensors' energy and processing power to provide adequate security in next generation WSN. The proposed protocols utilize Elliptic Curve Cryptography (ECC), Advanced Encryption Standard (AES), Certification Authority (CA), and Registration Authority (RA) to achieve a reasonable tradeoff.